Optimal analysis of material ratio for artificial rock by 3D printing technique - Wu, Tingting; Zhao, Hong; Xu, Quan; Zhao, Yixin (Geomechanics and geoengineering : an international journal, 2022)
Rock cores are important for rock properties research because they are linked to significant oil and gas drilling and production technology around the world. The goal of synthesising rock cores in the laboratory is to simulate the main factors of properties of reservoir rocks such as permeability, porosity and pore radius that can be used for tests in extreme conditions in replacement the high cost of obtaining natural cores. The reproduction of artificial rock cores in the laboratory also enables researchers to obtain samples with predetermined characteristics to better understand the relationship between their physical characteristics. In this paper, low-permeability and high-porosity artificial rock cores were made by 3D printing technology. The behaviour of the main petrophysical characteristics of these samples was investigated, such as setting time, rheology, permeability, porosity and compressive strength. The results were compared with natural samples and showed a high similarity to the petrophysical behaviour. By optimising the ratio of 3D printing materials, the physical properties of the samples were closer to the natural carbonate rocks. It provides a new technique and method to the development of special reservoir physical simulation experiments.